2000
DOI: 10.1021/es991057s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Humidity on the Chemical Composition of Secondary Organic Aerosol Formed from Reactions of 1-Tetradecene and O3

Abstract: The chemical composition of secondary organic aerosol formed in an environmental chamber from ozonolysis of 1-tetradecene in humid and dry air was determined using a thermal desorption particle beam mass spectrometer (TDPBMS). The major products are R-hydroxytridecyl hydroperoxide and bis(R-hydroxytridecyl) peroxide in humid air and symmetric C26 and asymmetric C14 secondary ozonides in dry air. The hydroperoxide is formed by reaction of stabilized Criegee biradicals with water vapor, and the peroxide (a perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 59 publications
3
116
2
1
Order By: Relevance
“…During the first several hours, the particle phase is dominated by first-to third-generation SVOCs, which are progressively converted to higher generation SVOCs in the gas phase and low volatility products in the particle phase. The contribution of particle-phase products to the total SOA budget is predicted to exceed 60% after ∼5 h. The dominance of low-volatility particle-phase products is consistent with previous studies, in which peroxyhemiacetals were found to be major products in SOA derived from oxidation of alkenes (1-tetradecene) (23,24), aromatic hydrocarbons (toluene) (25,26), and monoterpenes (α-and β-pinene) (27). Fig.…”
Section: Resultssupporting
confidence: 89%
“…During the first several hours, the particle phase is dominated by first-to third-generation SVOCs, which are progressively converted to higher generation SVOCs in the gas phase and low volatility products in the particle phase. The contribution of particle-phase products to the total SOA budget is predicted to exceed 60% after ∼5 h. The dominance of low-volatility particle-phase products is consistent with previous studies, in which peroxyhemiacetals were found to be major products in SOA derived from oxidation of alkenes (1-tetradecene) (23,24), aromatic hydrocarbons (toluene) (25,26), and monoterpenes (α-and β-pinene) (27). Fig.…”
Section: Resultssupporting
confidence: 89%
“…For example, our p 0 L,i prediction for pyruvic acid (CH 3 COCOOH) is excellent at both temperatures (Fig. 4), but a bias of one order of magnitude is obtained in the case of levulinic acid (CH 3 CO(CH 2 ) 2 COOH) at 320 K. A good agreement with the experimental data is obtained with our method for 2-hydroxy propanoic acid at 298 K. Tobias et al (2000) deduced the subcooled vapour pressure of α-hydroxytridecyl hydroperoxide on the basis of temperature-programmed thermal desorption (TPTD) analysis (3×10 −9±1 torr). The value predicted by our method for this hydroxy hydroperoxide is two orders of magnitude higher (see Fig.…”
Section: Minimization and Comparison With The Unifac Methodssupporting
confidence: 70%
“…Bonn et al based their estimations on UNI-FAC and on vapour pressure data for small hydroperoxides and for the C 13 hydroxy hydroperoxide measured by Tobias et al (2000). The exceptionally low vapour pressure of the latter compound has not been taken into account in our derivation of the hydroperoxy contribution, which might explain the discrepancy between our method and Bonn et al estimations.…”
Section: Minimization and Comparison With The Unifac Methodsmentioning
confidence: 76%
“…Recent studies of the oxidation of alkenes such as oleic acid particles and/or coated particles suggest that the CI can also react with carboxylic acids and alkenes to form larger compounds. [25][26][27][28][29][30][31][32] We report here the first observation of large organic aggregates on the surface generated in the ozone oxidation of terminal alkene SAMs. This surprising result shows that there is a previously unrecognized reaction mechanism for the ozonolysis of alkene SAMs, which has potentially important implications for the control of surface properties via oxidation of SAMs, and for the use of ozone as a cleaning agent for such surfaces.…”
Section: Introductionmentioning
confidence: 69%